Differences in the ignition characteristics of coal–water slurries and composite liquid fuel; Solid Fuel Chemistry; Vol. 50, iss. 2 - Vershinina K. Yu. Kseniya Yurievna; Glushkov D. O. Dmitry Olegovich; Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich (2016, 2016)
Title screen